Association of genetic variants in PDGFRA with high myopia in the Han population of southwestern China. (4th March 2022) - Jiang, Lingxi; Huang, Guo; Dai, Chao; Zheng, Rui; Xie, Chunbao; Duan, Suyang; Zhong, Ling; Liu, Xiaoqi; Gong, Bo; Yao, Dezhong; Yang, Zhenglin; Shi, Yi
ABSTRACT: Purpose: To investigate the associations of 11 genetic single nucleotide polymorphisms (SNPs) in FRAP1 and PDGFRA with high myopia (HM) in a Han Chinese population. Methods: A total of 442 HM patients and 947 healthy controls were recruited for this study. Five genetic models were analysed to further evaluate the association of target SNPs with HM. SNP functional annotation database tools were used to predict and analyse the potential function of these SNPs. Results: Our findings indicated that rs2114039 located in PDGFRA had significant association with HM in a Han Chinese population ( P = 2.00E-06, OR = 0.647, 95%CI = 0.542–0.773). The common genotypes rs2114039CC, rs2114039CT and rs2114039CT+TT all had a decreased risk of HM when compared with rs2114039TT ( P = 4.10E-05, OR = 0.290, 95%CI = 0.161–0.524; P = 1.00E-03, OR = 0.626, 95%CI = 0.479–0.819; P = 9.00E-06, OR = 0.560, 95%CI = 0.433–0.724, respectively). In addition, compared with rs2114039CT+TT, rs2114039CC also had a decreased risk of HM ( P = 3.59E-04, OR = 0.347, 95% CI = 0.194–0.620). Conclusions: Our findings indicated that rs2114039, located in PDGFRA, was significantly associated with HM in the southwest Han Chinese population. Additionally, rs2114039 might influence the function of PDGFRA by regulating the growth of human vision through different pathways. Furthermore, functional research on the role of PDGFRA in myopia pathogenesis should be conducted in the future.